REFLECTIONS ON RECONCILING RELIGIOUS BELIEF AND THE HISTORIAN'S CRAFT. - Kerry, Paul E. (Fides et historia, 2011)
The author reflects on the role of religious belief in historical study. His article responds to several essays published in the same issue, including "Mormon History Inside Out" by Richard Lyman Bushman, "Historians’ Metaphysical Beliefs and the Writing of Confessional Histories" by Brad S. Gregory, and "Coming to Terms as a Christian Historian with F. H. Bradley" by Mark A. Noll. Particular focus is given to the relationship between history and philosophy. It is suggested that historians may find it beneficial to explore the relationship between history and morality through an examination of philosophy. Other topics include historical empathy and historian Herbert Butterfield.